Bus voltage ranking and voltage stability enhancement for unbalanced multiphase networks - Juanuwattanakul, Parachai (Curtin University, 2012)
Voltage instabilities and subsequent system collapses are considered as growing concerns in modern multiphase distribution networks as they are progressively forced to operate closer to their stability limits due to many factors such as increasing load level, lack of reactive power sources, high installation of single-phase shunt capacitors and reverse action of voltage control devices. System operators must be able to quickly identify trouble spots and take corrective steps to avoid critical voltage collapses. To achieve this, suitable indices must be defined to assess system security and take corrective control actions when predefined thresholds are reached. In this regard, the identification and ranking of weak buses in a power system is an important research area.The existing conventional bus voltage ranking indices are only defined for single-phase and balanced three-phase networks. This thesis proposes a new bus voltage ranking index (VRI) to identify the weakest single-, two- and three-phase buses of multiphase distribution networks. Then, applications of the proposed bus ranking index will be tested for enhancing the voltage stability of unbalanced multiphase distribution networks.In the first part of this thesis, the definition of conventional voltage ranking indices are modified and generalized to also include unbalanced and multiphase networks using symmetrical components. For the first time, the method of symmetrical components is applied to the three-phase voltages computed from three-phase power flow. The new index is defined as the ratio of the (fundamental) positive-sequence voltage at the point of voltage collapse to the positive-sequence voltage at the base-load source. The former voltage level is determined by increasing the active power of all loads while keeping power factor constant until the point of voltage collapse is reached.In the second part of this thesis, the new VRI is validated through the calculation of grid losses and PV curves based on positive-sequence voltage. Extensive simulations of the IEEE 13 and 34 node test feeders are performed using the DIgSILENT PowerFactory to further validate and compare the performance of the new VRI with three well-known conventional ranking indices.In the third part of the thesis, the new VRI is used to identify the weakest three-phase buses in unbalanced three-phase distribution networks. Then, the index is utilized to place compensation devices at the weakest buses of the modified unbalanced three-phase 13 node test feeder to improve voltage stability and increase the maximum loading factor (MLF) under unbalanced three-phase operating conditions.In the fourth part of the thesis, static analyses are carried out to demonstrate applications of the proposed VRI in increasing MLF and improving voltage stability of multiphase networks under unbalanced loading and/or network conditions. Then, dynamic simulations are performed to further validate the accuracy of the proposed VRI and improving voltage stability under dynamic operating conditions.In the fifth part of the thesis, an online application of the proposed bus ranking is introduced to identify the weakest buses in multiphase smart grids with plug-in electric vehicle (PEV) charging stations.Finally, the proposed voltage ranking and stability enhancement approach are utilized to improve the performance of multiphase distribution networks by proper placement and sizing of distributed generator (DG) units such as doubly-fed induction generators (DFIGs) and single-phase capacitors. An iterative algorithm is proposed for the placement and sizing of DG units and single-phase capacitors in multiphase networks to reduce grid losses and increase MLF while keeping all bus voltages within acceptable limits. The approach consists of utilizing the positive- sequence voltage ratio Vcollapse/Vbase-load to identify the weakest three-phase and single-phase buses for the installation of DG units and shunt capacitors, respectively. DG penetration levels are increased (e.g., 40%) by evaluating their impacts on voltage profile, grid losses, and voltage stability margin while considering the voltage limits at all buses. The impacts of DIFG on voltage profile, active power loss, MLF and voltage unbalance factor are highlighted.